Islamic Economic Methodology Aproach to Achieve Economic Equity: Epistemological Study - Nur Azlina; R. Melda Maesarach; Muhammad Said (BASKARA : Journal of Business and Entrepreneurship, 2022)
Economic policies based on capitalism and socialism have proven to have failed to create a just economy. As a result of adhering to capitalist and socialist ideologies, macroeconomic imbalances and national instability occur. The welfare and prosperity of the people does not depend on production alone, but also on its proper distribution. Wealth in a country can be produced in large quantities, but if its distribution is not based on true and fair principles, then the country will not be able to achieve prosperity. This article aims to find out how the methodology of Islamic economics realizes equity and falah. This research uses descriptive qualitative research method with a literature review approach. Data collection techniques, with literature, from several sources obtained that are relevant to the theme. Books, journals, websites, and others. The data analysis technique is descriptive qualitative, describing the study of Islamic economic epistemology that can help realize economic equity. The results in this study BMT is a financial institutional system that is able to reform the conventional economic system and bring economic justice and equitable distribution with practical provisions through syar'i arrangements in collecting and distributing through wadi'ah, mudharabah, musyarakah, murabahah, salam, istishna transactions. , ijarah, and qardh. The implementation of Islamic social finance in Indonesia can be seen through the existence of various financial institutions that provide financial services by involving Islamic social funds such as Baznas (National Amil Zakat Agency), BWI (Indonesian Waqf Board) and other institutions with the aim of embracing the middle, small, and medium-sized micro communities.